CRESCIMENTO EM Albizia niopoides (Fabaceae) e Mabea fistulifera (Euphorbiaceae) SOB CONDIÇÃO DE ALAGAMENTO - PINHEIRO, Fernanda Polli; BRASIL, Joice Kely Vasconcelos; HOLSBACK, Zildamara dos Reis (ANAIS DO ENIC, 2018)
-